Comparison of three 3D scanning techniques for paintings, as applied to Vermeer’s ‘Girl with a Pearl Earring - Elkhuizen, Willemijn S.; Callewaert, Tom W. J.; Leonhardt, Emilien; Vandivere, Abbie; Song, Yu; Pont, Sylvia C.; Geraedts, Jo M. P.; Dik, Joris (Heritage science, 2019)
A seventeenth-century canvas painting is usually comprised of varnish and (translucent) paint layers on a substrate. A viewer’s perception of a work of art can be affected by changes in and damages to these layers. Crack formation in the multi-layered stratigraphy of the painting is visible in the surface topology. Furthermore, the impact of mechanical abrasion, (photo)chemical processes and treatments can affect the topography of the surface and thereby its appearance. New technological advancements in non-invasive imaging allow for the documentation and visualisation of a painting’s 3D shape across larger segments or even the complete surface. In this manuscript we compare three 3D scanning techniques, which have been used to capture the surface topology of Girl with a Pearl Earring by Johannes Vermeer (c. 1665): a painting in the collection of the Mauritshuis, the Hague. These three techniques are: multi-scale optical coherence tomography, 3D scanning based on fringe-encoded stereo imaging (at two resolutions), and 3D digital microscopy. Additionally, scans were made of a reference target and compared to 3D data obtained with white-light confocal profilometry. The 3D data sets were aligned using a scale-invariant template matching algorithm, and compared on their ability to visualise topographical details of interest. Also the merits and limitations for the individual imaging techniques are discussed in-depth. We find that the 3D digital microscopy and the multi-scale optical coherence tomography offer the highest measurement accuracy and precision. However, the small field-of-view of these techniques, makes them relatively slow and thereby less viable solutions for capturing larger (areas of) paintings. For Girl with a Pearl Earring we find that the 3D data provides an unparalleled insight into the surface features of this painting, specifically related to ‘moating’ around impasto, the effects of paint consolidation in earlier restoration campaigns and aging, through visualisation of the crack pattern. Furthermore, the data sets provide a starting point for future documentation and monitoring of the surface topology changes over time. These scans were carried out as part of the research project ‘The Girl in the Spotlight’.